Сучасні напрямки наукової діяльності Українського науково-дослідного інституту пожежної безпеки МНС України (огляд) - Откідач, М.Я.; Сопенко, С.І. (Актуальні проблеми транспортної медицини, 2006)
редставлена обзорная информация об Украинском научно-исследовательском институте пожарной безопасности МЧС Украины и основных направлениях его деятельности. Обговорены проблемы токсикологии горения как одной из составляющих методологии проведения комплекса испытаний на пожарную опасность. Рассмотрены возможные дальнейшие пути внедрения новых подходов, основанных на изучении влияния токсичности продуктов сгорания на функциональную эффективность пожарных и спасателей. The survey information on the Ukrainian scientific research fire-safety institute of the ME of Ukraine and the basic directions of its activity is presented. Problems for burning toxicology are discussed as one of the components, related to methodology of the fire-hazard complex tests carrying out. Possible further ways of the new approaches introduction, based on studying of combustion products toxicity influence on firemen and rescuers functional efficiency are considered.